1978
DOI: 10.1128/aac.13.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Netilmicin: Clinical Efficacy, Tolerance, and Toxicity

Abstract: Netilmicin, a new aminoglycoside antibiotic, has increased in vitro bactericidal activity against many strains of Enterobacteriaceae as compared to other aminoglycosides. It is a poor substrate for some of the common gentamicin-inactivating enzymes, and it has minimal toxicity in experimental animals. In 27 hospitalized patients, clinical cure was achieved in all, and the initial infecting organism persisted in only one. Therapeutic serum and urine levels were easily obtained in most patients. No ototoxicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 9 publications
4
13
0
Order By: Relevance
“…We attribute this variability to the changing physiological status of postoperative patients, with fluctuating levels of hydration, renal function, and cardiovascular function. These levels are comparable to those reported by others (7,12,16). In seriously ill patients, a dose of 2.5 mg/kg every 8 h would appear to afford adequate levels more regularly than 2 mg/kg.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We attribute this variability to the changing physiological status of postoperative patients, with fluctuating levels of hydration, renal function, and cardiovascular function. These levels are comparable to those reported by others (7,12,16). In seriously ill patients, a dose of 2.5 mg/kg every 8 h would appear to afford adequate levels more regularly than 2 mg/kg.…”
Section: Resultssupporting
confidence: 88%
“…In no instance did the alkaline phosphatase abnormality persist. As noted by Panwalker et al, who found alkaline phosphatase elevations in 40% of their patients, the etiology and significance of this finding deserves further study (12).…”
Section: Antimicrob Agents Chemothersupporting
confidence: 52%
See 1 more Smart Citation
“…Table 1 shows the concentrations of gentamicin and netilmicin in the serum after 1, 3, or 14 10-mg/kg injections of either drug. The serum levels of both aminoglycosides were identical and similar to those found in humans (9,17). The half-lives of the two antibiotics in serum were not clinically different (Table 2).…”
Section: Methodssupporting
confidence: 73%
“…We studied a large number of critically ill patients who received aminoglycoside antibiotics by appropriate dosing schedules, and we (10,12,20,21) in humans, although in rats, netilmicin is consistently less nephrotoxic (1,9,11). Third, our nephrotoxic patients showed abnormal tissue uptake early in treatment, before changes in serum creatinine occurred.…”
Section: Discussionmentioning
confidence: 99%